The Effect of an Eight-week Pilates Training on Interleukine-18 Level, Fatigue, and Balance in Women With Multiple Sclerosis - Soodabeh Asvar; Farzaneh Taghian (Gonabad University of Medical Sciences, 2020)
Background: Proinflammatory cytokines increasingly cause inflammation in patients with Multiple Sclerosis (MS). In this regard, the current study aimed to shed light on the effectiveness of an eight-week Pilates training program in the level of interleukin-18, the severity of fatigue, balance, and physical disability, in females with MS. Methods: This study was a quasi-experimental research with a pre-test-post-test design and a control group and conducted in Sirjan City, Iran. A total of 30 female MS patients (Mean±SD age: 30.15±6.97 years; 2≤ expanded disability status scale≤5.5) were selected using a purposeful sampling method and divided into control and experimental groups. The experimental group conducted the Pilates exercises for eight weeks, three sessions per week (lasting 45-60 minutes), while the control group had no regular physical activity. Before and after the training program, we evaluated fatigue, physical disability, and balance using the fatigue severity scale, the expanded disability status scale, and the Berg balance scale, respectively. Also, 5 mL of blood was taken from each participant to evaluate the interleukin-18 level. Then, the independent t-test was used to compare the pretest-posttest scores. Results: The findings indicated that the Pilates training program significantly decreased the level of interleukin-18, the severity of fatigue, and the score of physical disability (P≤0.05), and increased the balance (P≤0.05), in females with MS. Conclusion: Therefore, patients with MS can make the best use of such exercises to strengthen their immune systems and performances.